Software de Modelización Hidráulico en Canales (2017)
Hydraulic channels are natural or artificial structures that transport a determined water course and that, unlike the pipe complexes, are open to the atmosphere. For this reason, this article aims to show the traditional hydraulic modeling techniques along with the most relevant hydraulic modeling software of today, making known their operation, advantages and disadvantages of each one of them. The information presented in the article is a compilation of information for the development of the article. HEC-RAS is undoubtedly one of the most important hydraulic modeling software in the world because it combines a series of efficient elements that make the program one of the most efficient on the market, however there are other modeling software, original Europe as SOBEK and MIKE 11 which are efficient according to certain parameters previously provided by the user, however its efficiency is not in doubt by being optimal in several design and study environments such as the rural, urban and fluvial sector.